Catherinum anglicum Gale 2016, SP. NOV. - Gale, Andrew Scott (Zenodo, 2016)
CATHERINUM ANGLICUM SP. NOV. FIGURE 19C–K, N–Q, T, V Diagnosis Catherinum in which the occludent margin of the tergum is straight, and the external surface adjacent to this carries three ribs that diverge from the umbo. The upper part of the upper latus margin of the scutum is embayed. The carinolatus has a very broad upper latus margin. Derivation of name After East Anglia, in which the type material was collected. Material Fifty valves, including carinae, scuta, terga, and carinolatera, from the upper Campanian, Belemnitella mucronata zone chalk of Keswick and Cringleford Newfound Farm pits, Norwich, Norfolk, UK. The scutum illustrated is the holotype (Figure 19O), and the other illustrated valves are paratypes. Description The carina (Fig. 19E, I, P, T, V) is gently incurved towards the tergum, and the parietes are of even width; intraparietes are not developed. The tectal ridges are robust and broad (Fig. 19E, T), and the tectal surface between these is slightly convex. The tergum (Fig. 19Q) is elongated and triangular, and the carinal margin is slightly convex. Three radial ridges run from the umbo, subparallel with the occludent margin. The scuta (Fig. 19J, K, N, O) are concavo–convex, trapezoidal, and the umbo is pointed and incurved; the upper latus margin has a distinctive concavity just beneath the tergal–upper latus angle. A narrow groove runs parallel with the occludent margin. On the interior of the valve, a deep, oval dwarf male receptacle lies between the apex and the scutal adductor scar. The carinolatus (Fig. 19C, D, F–H) has a low, incurved umbo, and a tall carinal margin. The long, straight upper latus and inframedian latus margins are set at right angles. The plate is very typical of Catherinum of the Ca. hispidum (Fig. 19A, B) and Ca. striolatum (Fig. 7P, Q) type. Remarks Catherinum anglicum sp. nov. is perhaps closest to the extant Ca. hispidum from the Norwegian Sea. The carinae are very similar indeed, both carrying very broad, robust tectal ridges (Fig. 19I, S, T), and with shallow short ...